A comprehensive investigation on U-tube ground heat exchanger performance considering insulation layer in deep geothermal system. (June 2022) - Xu, Ningning; He, Miao; Xu, Mingbiao; Chen, Huan
Abstract: This study established a full-size coupling model of unsteady flow and heat transfer between U-tube and ground considering the insulation layer, which was solved by the finite volume method. The model's reliability was validated through experimental data of geothermal U-tube in Xi'an. The maximum relative error of this model was 6.46% in 2–6 h, and the average relative error was 0.51% in 7–72 h. This model performed better than the other two models published. According to the outlet temperature, thermal power, quantity of heat, and the temperature distribution of the U-tube at different insulation depths, the optimal insulation depth was the intersection of the ground temperature and the temperature curve in the tube and the insulation depth was 1615.85 m. Analyzed the influence of flow rate and other parameters on outlet temperature and thermal power, the sensitivity of each factor to heat extraction power was obtained by orthogonal test. The results showed that the flow rate was the most sensitive factor to thermal power, and the percentage loss of water and the thermal conductivity of rock were generally sensitive to thermal power. This study could provide a theoretical reference for developing and utilizing u-tube geothermal in deep layers.